Equitable access to digital higher education for students with disabilities in South Africa - Johannes N. Zongozzi; Sindile A. Ngubane (African Journal of Disability, 2025)
Background: The growing reliance on digital learning in South Africa, partly because of the emergence of the coronavirus disease 2019 (COVID-19) and 4IR technologies, risks excluding students with disabilities (SwDs) if measures to adequately support them are not in place.